Determinants of Firm Value in Food & Beverage Companies Listed on the IDX in 2019-2022 - Fitir Riasi, Fatikhah; Purwidianti, Wida; Handayani, Erna; Endratno, Hermin (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the influence of Profitability, Capital structure, GCG, Firm size, and Firm Age on Firm Value. This research uses quantitative methods with secondary data types, the population are 26 food & beverage companies registered on the IDX in 2019-2022, and a sample size of 83 companies was obtained from purposive sampling techniques with unbalanced panel data. The data processing results using SPSS Statistics 26 show that profitability positively and significantly affects Firm value. Capital Structure, GCG, Firm Size, and Firm Age have no impact on Firm Value.